2021
DOI: 10.3390/plants10122756
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Characterization of GhCOMT Gene Family during Fiber Development and Verticillium Wilt Resistance in Cotton

Abstract: Caffeic acid O-methyltransferases (COMTs) play an essential role in lignin synthesis procession, especially in the plant’s phenylalanine metabolic pathway. The content of COMT genes in cotton and the relationship between their expression patterns have not been studied clearly in cotton. In this study, we have identified 190 COMT genes in cotton, which were classified into three groups (I, II and III), and mapped on the cotton chromosomes. In addition, we found that 135 of the 190 COMT genes result from dispers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 62 publications
0
1
0
Order By: Relevance
“…The preferred substrates of COMT are caffeoyl aldehyde and 5-hydroxyconiferaldehyde [ 25 , 46 ]. According to the annotation of metabolic pathways in transcriptome sequencing, it is known that in the accumulation of scopoletin in noni, the transformation from caffeic acid to ferulic acid was realized.…”
Section: Discussionmentioning
confidence: 99%
“…The preferred substrates of COMT are caffeoyl aldehyde and 5-hydroxyconiferaldehyde [ 25 , 46 ]. According to the annotation of metabolic pathways in transcriptome sequencing, it is known that in the accumulation of scopoletin in noni, the transformation from caffeic acid to ferulic acid was realized.…”
Section: Discussionmentioning
confidence: 99%
“…St4CL contains a highly conserved SGTT-PKGV (Ser Gly Thr Thr-Pro Lys Gly Val) amino acids in AMP-binding domain (Figure S3a) (Mo et al, 2022) and is clustered with Nt4CL1, which has been proved to regulate the biosynthesis of phenolic compounds in Nicotiana tabacum (Figure S3b) (Zhao et al, 2016). Similarly,StOMT contains a conserved domain (SAM binding site, Figure S4a) (Wu et al, 2021) and is clustered with AtOMT7, which has been proved to take part in the biosynthesis of lignin in Arabidopsis (Figure S4b) (Raes et al, 2003).RT-qPCR results showed that wounding significantly upregulated the expression of StPAL, StOMT, and St4CL, which were 182-, 41-, and 142-fold higher at 1 day than that at 0 day, respectively (Figure 3b-d). After wounding, the expression of these three genes remained at high levels, and the expression levels at the early stage (1 day) were slightly higher than those at the late stage (7 days).…”
Section: Screening the Suberin Biosynthesis-related Target Genes In T...mentioning
confidence: 99%